Toxicity of dietary restriction of fat enriched diets on cardiac tissue - Diniz, Y. S.; Faine, L. A.; Almeida, J. A.; Silva, MDP; Ribas, B. O.; Novelli, ELB (Elsevier B.V., 2002)
The present study examines the effects of caloric restriction in cardiac tissue evaluation markers of oxidative stress. High-fat dietary restrictions can have a long-term impact on cardiac health. Dietary restriction of control diet increased myocardial superoxide dismutase (SOD) and catalase activities. Dietary restriction of fatty acid-enriched diets increased myocardial lipoperoxide concentrations, while SOD activity was decreased in cardiac tissue of rats with dietary restriction of fatty acid-enriched diets. Dietary restriction of unsaturated fatty acid-enriched diet induced the highest lipoperoxide concentration and the lowest myocardial SOD activity. Dietary restriction of unsaturated fatty acid decreased myocardial glycogen, and increased the lactate dehydrogenase/citrate synthase ratio. Dietary restriction of fatty acid-enriched diets were more deleterious to cardiac tissue than normal ad lib.-fed diet. In conclusion, the effects of caloric restriction on myocardial oxidative stress is dependent on which nutrient is restricted. Dietary restriction of fatty acid-enriched diets is deleterious relative to ad lib.-fed chow diet. (C) 2002 Elsevier, Science Ltd. All rights reserved.
Keywords: heart; dietary restriction; fatty acid; enzymes; oxidative stress